Panti Jompo dengan Pendekatan Healing Environment di Denpasar - Shinta Mustika Dewi Wijaya; I Gede Surya Darmawan; I Wayan Wirya Sastrawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Bali is one of the provinces with the 4th largest elderly population in Indonesia. Denpasar City has a number of neglected elderly people as many as 416 people which causes a lack of elderly housing facilities. The increase in the number of neglected elderly people in Bali is still neglected from a social, cultural and psychological perspective and for example, the Wana Seraya Denpasar PSTW still shows that 50% of respondents experience depression and 50% of respondents live with poor quality. From a field survey in several nursing homes in Bali it is still not feasible to support the activities of the elderly based on existing standards. The purpose of this research is to analyze the characteristics of users, types of main rooms, be able to apply the concept of healing environment, and design themes, and be able to formulate planning and design concepts in the designed nursing home. Descriptive qualitative research method to determine natural conditions and researchers go directly to the field with the object of research so as to describe the data obtained clearly and in accordance with the conditions in the field. The results of this study are the provision of a residential facility, mental and physical health facilities, spiritual facilities for getting closer to oneself and a creative vessel that can improve the physical and psychological conditions of the elderly who have experienced a deteriorating condition with environmental assistance and pay attention to other architectural elements.